The level at which registered nurses utilise the nursing process in local-level primary health care practice in Namibia - Iita, Hermine; Iipinge, Scholastika; Van Dyk, Agnes (International Journal of Advanced Nursing Studies, 2016)
The purpose of this study was to explore and describe the use of the Nursing Process by registered nurses in local level primary health care practice in Namibia. The findings were used to serve as a basis to develop strategies to support registered nurses in their daily local PHC practice. A quantitative research approach using a survey design with self-report questionnaire was used. The population consisted of two groups. The first group consisted of 239 registered nurses working in Clinics, health Centers and in Outreach Programs. The second group consisted of 39 registered nurses supervisors of the registered nurses in these facilities. Quantitative, descriptive analysis was used to summarize and organize data using tables and figures as well as t-test and analysis of variance (ANOVA), where applicable. Five main problem areas were identified. It was concluded that strategies needed to be developed to support registered nurses in their daily local Primary health care practice. The development of strategies will be dealt with in a different paper.